Prostate-Specific Antigen Screening According to Health Professional Counseling and Age in the United States - Ray M. Merrill; Seth A. Otto; Eliza B. Hammond (Prostate Cancer)
Background. In 2018, the US Preventive Services Task Force recommended that PSA screening for prostate cancer involve men aged 55–69, based on a personal decision following consultation with a health professional. PSA screening in men aged 70 or older should only occur if symptoms exist. This study identifies the association between having a PSA test in the past two years and whether or not there was consultation with a health professional about the benefits and/or harms of PSA screening. Methods. Analyses were based on data involving men aged 40 years or older, who responded to PSA related questions in the 2018 BRFSS survey. Results. Approximately 32.0% (14.6% for ages 40–54, 41.7% for ages 55–69, and 49.8% for ages 70 years and older) of respondents had a PSA test in the past two years. Approximately 81.7% of these men had talked with a health professional about the benefits and/or harms of PSA screening, with 42.4% having discussed the benefits and harms, 54.6% having discussed the benefits only, and 3.0% having discussed the harms only. The odds of a PSA test in the past two years in men having talked with a health professional about the benefits and harms of the test versus no talk are 10.1 (95% CI 9.3–10.8), in men who talked with a health professional about the benefits only versus no talk are 10.8 (95% CI 10.0–11.6), and in men who talked with a health professional about the harms only versus no talk are 3.9 (95% CI 2.9–5.1). Conclusion. PSA screening is most common in men aged 70 or older, which is counter to the US Preventive Task Force recommendation. Most men having a PSA test have talked with a health professional about the test, but the talks tended to focus on just the benefits of screening and not both potential benefits and harms.